Gender Equality Issues in Optical Feminist Jurisprudence and Implementation in Indonesian - Heri Setiawan; Steven Ouddy; Mutiara Girindra Pratiwi (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Gender meaning of fundamentally different from biological sex. Biological sex is a gift; we are born as a man or a woman. However, the path that makes us masculine or feminine is a combination of the building blocks of basic biological and biological interpretation by our culture. From the tiny baby to reach old age, we learn and practice specific ways that have been determined by the community for us to be men and women. Gender is a set of roles as well as costumes and masks at the theater, convey to others that we are feminine or masculine. Device specific behaviors include appearance, dress, attitude, personality, work inside and outside the household, sexuality, family responsibilities and so together polish "gender roles" us. If someone mentions or asks about gender, then what is meant is gender in the context of language approach. This term became very commonly used in the last few decades. Feminist jurisprudence is a legal philosophy that is based on gender equality in politics, economic and social. Feminist jurisprudence unpacks and explain how the law plays a role to legalize the status of women in subordination to men, in other words, the law as a means to preserve the status quo, namely the dominance of men over women. Moreover, feminist jurisprudence is also trying to make a change/transformation changing the status of women by changing laws and its approach and its stance on gender cases be more fair and balanced. This is an emancipatory project woman in law. Keywords: Gender; Feminist Jurisprudence; justice; men and women.